Correlation of IP-10 gene expression with Serum alanine transaminase (ALT) levels and Hepatitis B viral load in cirrhosis and hepatocellular carcinoma (HCC) patients. - Shahera, Umme; Alam, Shahinul; Jahan, Munira; Nessa, Afzalun; Munshi, Saifullah; Tabassum, Shahina (Bangladesh Journal of Medical Microbiology, 2016)
Interferon-gamma induced protein 10 (IP-10), a chemokine is suggested to be involved in liver injury during Hepatitis B virus infection (HBV). The increase of IP-10 is a critical step for recruitment of inflammatory cells to the local focus of the liver and hepatopathology. This study was designed to assess the correlation of IP-10 gene expression with HBV-DNA and serumAlanine transaminase(ALT) in patients with cirrhosis and HCC.The study was conducted among 60 patients. The study populationwere divided into four groups (15 in each groups)-HBV positive cirrhosis, HBV negative cirrhosis, HBV positiveHCC and HBV negative HCC. Expression of IP-10 gene was observed using real time PCR.IP-10 gene expressions in the above mentioned groups were correlated with serum ALT level and HBV viral load.IP-10 gene was significantly higher in HBV-positive patients with HCC than HBVpositive cirrhosis. Similarly, the expression of IP-10 was significantly higher in HBV-positive HCC than HBVnegative HCC patients. However, the expression of IP-10 was reduced in HBV-positive cirrhosis in comparison with HBV-negative cirrhosis.IP-10 gene expression in liver was not correlated with the serum levels of ALT in any of the study groups. HBV- DNA load also did not correlated with IP-10 gene expression in HBV positive HCC and HBV positive cirrhosis patients.This study shows that there was no significant change with the expression of IP-10 gene in any of the study groups with ALT level or viral load, though differential expression of IP-10 gene were observed in cirrhosis and HCC patients. Bangladesh J Med Microbiol 2016; 10 (2): 9-13